Pembinaan Prestasi Olahraga Sepak Bola Pada SSB 18 Di Kabupaten Jepara Tahun 2021 (Universitas Negeri Semarang, 2021)
The purpose of the research is a Development of Football Sports Achievement at SSB 18 in districts of Jepara. This research uses a qualitative ethnography approach. Collecting data using the method of observation, interviews, and documentation. The subjects of this study were the management, coaches, and athletes of the 18 SSB. The data analysis technique used was data triangulation technique. Data analysis with data reduction, data presentation, and withdrawal. The results of the research that have been carried out show that, the stages of fostering soccer achievements at the 18 SSB in the districts of Jepara include the stages of installation, breeding and achievement. The management of the 18 SSB organization has been running according to their respective main duties and functions and has an active role in fostering soccer achievements. The training program at SSB 18 is in a good category, each trainer has a training program that is quite effective and efficient. The trainers at SSB 18 can be said to be good, they have the enthusiasm and purpose to train. The soccer athletes at SSB 18 are good enough both in teams and individually and have a good attitude. The facilities and infrastructure at SSB 18 are quite good and according to standards. Funding at SSB 18 comes from student registration fees and student monthly tuition fees. From the results of the research, it can be concluded that the implementation of soccer sport development in SSB 18 is good enough.